Kajian Identifikasi Teknik Propaganda yang Menguatkan dan Melemahkan Anies Baswedan di Pemilihan Presiden Tahun 2024 - Sapta Wira Udaya; Hariyanto (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Political communication is all types of communication aimed at politics. Political communication can be done in various forms, such as rhetoric, political agitation, propaganda, public relations, political campaigns, political lobbying, and others. Propaganda is a technique of influencing human actions by manipulating representations in oral, written, pictorial or musical form. Seven propaganda techniques that are often used, including in politics, are name calling, generalities glittering, testimonial transfer, plain folks, card stacking, and bandwagon. As one of the presidential candidates participating in the 2024 Presidential Election contest,  there come a lot of propaganda to Anies Baswedan. This study is to find out what propaganda is happening to Anies Baswedan, both strengthening and weakening. The method used in the study is descriptive qualitative. The data processed is in the form of data/information from media analysis and the results of interviews with related informants. The results of the study show that there are several propaganda techniques that strengthen and weaken Anies Baswedan, even though further research is still needed to find out the influence of each propaganda technique on Anies Baswedan's defeat in the 2024 Presidential Election. The success of propaganda is greatly influenced by mass media, especially social media using by propagandists.